Spectroscopic Identification and Photochemistry of Astrochemically Relevant Phosphorus-bearing Molecules [O, C, N, P] and [2O, C, N, P] - Bifeng Zhu; Minghao Wang; Junjie Jiang; Ningjing Jiang; Jingling Hong; Guntram Rauhut; Guanjun Wang; Weixing Li; Xiaoqing Zeng (The Astrophysical Journal, 2024)
Diatomic molecules phosphorus monoxide (PO) and phosphorus mononitride (PN) are the main reservoirs of gas-phase phosphorus in interstellar and circumstellar environments, indicating the possibility of forming new phosphorus-bearing molecules through reactions with other interstellar species. To explore the astrochemistry of PO and PN, new simple phosphorus-bearing molecules [O, C, N, P] and [2O, C, N, P] were generated in the gas phase and isolated in cryogenic matrices for characterization with matrix-isolation IR and UV/vis spectroscopy in combination with calculations at the CCSD(T)-F12a/VTZ-F12 level of theory. In an inert argon matrix, OPCN isomerizes to OPNC upon UV-light irradiation at 365 nm, followed by successive isomerizations to PNCO and POCN with concomitant dissociation to diatomic PN and CO under further irradiation at 193 nm. By analogy, the isomerization of O _2 PCN to O _2 PNC and OPNCO followed by fragmentation to OPN/CO and PN/CO _2 occurs in the matrix upon irradiation at 193 nm. In a chemically active CO ice, the photolytic reaction of OPCN with CO yields CO _2 and PCN, and O _2 PCN reacts with CO by forming OPCN and CO _2 , in which the photochemical networks for these P-bearing species linking the astrochemically important PN and PO have been proposed. The experimental identification of these phosphorus-bearing molecules is supported by quantum chemical calculations, and the spectroscopic data may aid in their detection in the interstellar and circumstellar medium.